Managing temperate forests for carbon storage: impacts of logging versus forest protection on carbon stocks. Issue 6 (25th June 2014) - Keith, Heather; Lindenmayer, David; Mackey, Brendan; Blair, David; Carter, Lauren; McBurney, Lachlan; Okada, Sachiko; Konishi-Nagano, Tomoko
Abstract : Management of native forests offers opportunities to store more carbon in the land sector through two main activities. Emissions to the atmosphere can be avoided by ceasing logging. Removals of carbon dioxide from the atmosphere can be increased by allowing forests to continue growing. However, the relative benefits for carbon storage of managing native forests for wood production versus protection are contested. Additionally, the potential for carbon storage is impacted upon by disturbance events, such as wildfire, that alter the amount and longevity of carbon stocks. Using a case study of montane ash forests in southeastern Australia, we demonstrated that the total biomass carbon stock in logged forest was 55% of the stock in old growth forest. Total biomass included above‐ and belowground, living and dead. Biomass carbon stock was calculated spatially as an average across the landscape, accounting for variation in environmental conditions and forest age distribution. Reduction in carbon stock in logged forest was due to 66% of the initial biomass being made into products with short lifetimes (<3 years), and to the lower average age of logged forest (<50 years compared with >100 years in old growth forest). Only 4% of the initial carbon stock in the native forest was converted to sawn timber products with lifetimes of 30–90 years. Carbon stocks are depleted in a harvested forest system compared with an old growth forest, even when storage in wood products and landfill are included. We estimated that continued logging under current plans represented a loss of 5.56 Tg C over 5 years in the area logged (824 km 2 ), compared with a potential gain of 5.18–6.05 TgC over 5 years by allowing continued growth across the montane ash forest region (2326 km 2 ). Avoiding emissions by not logging native forests and allowing them to continue growing is therefore an important form of carbon sequestration. The mitigation value of forest management options of protection versus logging should be assessed in terms of the amount, longevity and resilience of the carbon stored in the forest, rather than the annual rate of carbon uptake.